Anti-inflammatory activities and potential mechanisms of phenolic acids isolated from Salvia miltiorrhiza f. alba roots in THP-1 macrophages. (10th August 2018) - Liu, Haimei; Ma, Shuli; Xia, Hongrui; Lou, Hongxiang; Zhu, Faliang; Sun, Longru
Abstract: Ethnopharmacological relevance: The roots of Salvia miltiorrhiza f. alba (Lamiaceae) (RSMA) are used as the Danshen, a traditional Chinese medicine, to treat the vascular diseases at local clinics, especially for the remedy of thromboangiitis obliterans (TAO) more than 100 years. Phenolic acids are one of the major effective constituents of RSMA, and some studies have linked phenolic acids with anti-inflammatory functions. Aim of the study: The purpose of this research was to isolate phenolic acids from RSMA and investigate their anti-inflammatory effects and potential mechanisms. Materials and methods: Nine already known compounds were obtained from RSMA. Their structures were elucidated through the spectroscopic analysis and comparing the reported data. The anti-inflammatory effects and potential mechanisms were investigated in LPS-stimulated THP-1 cells, using salvianolic acid B (SalB) as the positive control. The enzyme-linked immunosorbent assays (ELISA) were used to determine the secretory protein levels of interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). And quantitative real-time polymerase chain reaction (qRT-PCR) was used to analyze the mRNA levels of these inflammatory cytokines. The expression of TLR4, p65, p-p65, IκBα, and p-IκBα were measured using western blot. Results: All these compounds, except for rosmarinic acid (5 ) and isosalvianolic acid (6 ) for IL-6 protein levels, rosmarinic acid-o-β-D-glucopyranoside (3 ) for IL-6 mRNA, and rosmarinic acid-o-β-D-glucopyranoside (3 ), rosmarinic acid (5 ) and isosalvianolic acid (6 ) for TNF-α mRNA levels, remarkably inhibited the production of TNF-α, IL-1β, and IL-6 at the concentration of 5 and 25 μM in the mRNA and protein levels. Lithospermic acid (7 ) showed the strongest inhibitory effect among them and was similar to that of SalB. In particular, lithospermic acid (7 ) and SalB markedly downregulated the expressions of TLR4, p-p65, and p-IκBα induced by LPS in THP-1 macrophages. Conclusions: All the phenolic acids displayed anti-inflammatory properties and the potential mechanisms involved the TLR4/NF-κB signal pathway. Results of this study indicate that phenolic acids may be effective constituents of RSMA to treat vascular diseases associated with inflammation. Graphical abstract: